FOREST WORKS OF THE BASHKIR OF THE INZERIAN BASIN (END OF THE 19TH - THE BEGINNING OF THE 21ST CENTURIES) - Hasanova, Zulejha Favadisovna (History, Archeology and Ethnography of the Caucasus, 2018)
The paper, on the basis of the analysis of ethnographic and archival materials, considers the features of the development of forest crafts among the Bashkirs of the Inzersky Basin, according to tribal composition related to the Katayans (Inzer-, Kuzgun-, Idel-Katayans) in the chronological framework of the study from the middle of the 19th century until now. Expeditions were carried out in 2010-2011, 2016-2017. in 13 Bashkir settlements of Beloretsk region of the Republic of Bashkortostan (hereinafter - RB). When writing the paper, archival materials of the National Archives of the Republic of Bashkortostan (Ufa) (hereinafter - «the Republic of Bashkortostan») were used. Forestry of the Bashkirs of the Inzersky Basin began to develop in the 17th - early 18th centuries and widely spread in the middle of the 19th century. They included: logging and rafting logs (main occupation), harvesting various kinds of raw materials, pitching tars, drenching bogs, carbonation. The Bashkirs lumbered, both in their own and in national country-plots - dachas. They provided with firewood Beloretsk, Tirliansk, Inzersk, Lapishtinsk, Zigazinsk, Avziano-Petrovsk, Uzyan, Kaginsk plants. Men were those who mainly worked, although during the war and the postwar years in some industries there worked women and adolescents: in getting materials for driving tar, in the process of scrubbing bast. It was all-year-round work, in winter they cut down forests and took them to the rafting rivers. In spring they rafted the forest, got resin, and made bast. From spring to autumn carbonation was carried out. Currently, in the settlements of Tukan, Zigaza, Maigashle, coal is produced for sale in traditional way. From linden bark they got the bast. From the bast they made ropes, mattresses, and harnesses. When writing the article, the author took into account that the peoples of the Caucasus had the similar forestry trades. In this regard, the study will be useful in the comparative-historical context.